Hydrogen Peroxide and Sodium Transport in the Lung and Kidney. (17th March 2016) - Shlyonsky, V.; Boom, A.; Mies, F.
Abstract : Renal and lung epithelial cells are exposed to some significant concentrations of H2 O2 . In urine it may reach 100 μ M, while in the epithelial lining fluid in the lung it is estimated to be in micromolar to tens-micromolar range. Hydrogen peroxide has a stimulatory action on the epithelial sodium channel (ENaC) single-channel activity. It also increases stability of the channel at the membrane and slows down the transcription of the ENaC subunits. The expression and the activity of the channel may be inhibited in some other, likely higher, oxidative states of the cell. This review discusses the role and the origin of H2 O2 in the lung and kidney. Concentration-dependent effects of hydrogen peroxide on ENaC and the mechanisms of its action have been summarized. This review also describes outlooks for future investigations linking oxidative stress, epithelial sodium transport, and lung and kidney function.